Autophagy: Regulator of cell death - Liu, ShiZuo; Yao, ShuaiJie; Yang, Huan; Liu, ShuaiJie; Wang, YanJiao (Cell death & disease, 2023)
Autophagy is the process by which cells degrade and recycle proteins and organelles to maintain intracellular homeostasis. Generally, autophagy plays a protective role in cells, but disruption of autophagy mechanisms or excessive autophagic flux usually leads to cell death. Despite recent progress in the study of the regulation and underlying molecular mechanisms of autophagy, numerous questions remain to be answered. How does autophagy regulate cell death? What are the fine-tuned regulatory mechanisms underlying autophagy-dependent cell death (ADCD) and autophagy-mediated cell death (AMCD)? In this article, we highlight the different roles of autophagy in cell death and discuss six of the main autophagy-related cell death modalities, with a focus on the metabolic changes caused by excessive endoplasmic reticulum-phagy (ER-phagy)-induced cell death and the role of mitophagy in autophagy-mediated ferroptosis. Finally, we discuss autophagy enhancement in the treatment of diseases and offer a new perspective based on the use of autophagy for different functional conversions (including the conversion of autophagy and that of different autophagy-mediated cell death modalities) for the clinical treatment of tumors.